Shiga toxin-producing Escherichia coli in beef retail markets from Argentina - Brusa, Victoria; Aliverti, Virginia; Aliverti, Florencia; Ortega, Emanuel E.; de la Torre, Julián H.; Linares, Luciano H.; Sanz, Marcelo; Etcheverría, Analía I.; Padola, Nora Lía; Galli, Lucia; Peral García, Pilar; Copes, Julio A.; et al. (Frontiers in Cellular and Infection Microbiology, 2013)
Shiga toxing-producing Escherichia coli (STEC) are foodborne pathogens that cause mild or serious diseases and can lead to people death. This study reports the prevalence and characteristics of STEC O157 and non-O157 in commercial ground beef and environmental samples, including meat table, knife, meat mincing machine and manipulator hands (n= 450) obtained from 90 retail markets over a nine-month period. The STEC isolates were serotyped and virulence genes as stx (Shiga toxin), rfbO157 (O157 lipopolysaccharide), fliCH7 (H7 flagellin), eae (intimin), ehxA (enterohemolysin) and saa (STEC autoagglutinating adhesin), were determined. STEC O157 were identified in 23 (25.5%) beef samples and 16 (4.4%) environmental samples, while STEC non-O157 were present in 47 (52.2%) and 182 (50.5%), respectively. Among 54 strains isolated, 17 were STEC O157:H7 and 37 were STEC non-O157. The prevalent genotype for O157 was stx2/eae/ehxA/fliCH7 (83.4%), and for STEC non-O157 the most frequent ones were stx1/stx2/saa/ehxA (29.7%); stx2 (29.7%); and stx2/saa/ehxA (27%). None of the STEC non-O157 strains were eae-positive. Besides O157:H7, other 20 different serotypes were identified, being O8:H19, O178:H19 and O174:H28 the prevalent. Strains belonging to the same serotype could be isolated from different sources of the same retail market. Also, the same serotype could be detected in different stores. In conclusion, screening techniques are increasingly sensitive, but the isolation of STEC non-O157 is still a challenge. Moreover, with the results obtained from the present work, although more studies are needed, cross-contamination between meat and the environment could be suspected.